La Unedited Gaze: Kawésqar Women and Men in the journal and watercolours of Lieutenant Vereker (H.M.S. Alert, 1879) - Harambour, Alberto (Universidad Católica del Norte, Instituto de Investigaciones Arqueológicas y Museo, 2020)
The Royal Navy’s officer F.C.P. Vereker did like to paint, and he did live on board between 1865 and 1884. Since he was 15 and up to his 34 he travelled through the world engaging in different tasks, as sounding the coasts of Patagonia and Australia, or bombing the port of Fort Jesus, in current Kenya. In most of his destinations, Vereker painted watercolours, and wrote down his impressions about them and the peoples who inhabited there. Almost all of his manuscripts of fine calligraphy and attached small paintings are located at the Royal Geographical Society, in London, and all of them remain unpublished. In this article I do present for the first time Vereker’s double register, visual and textual, of his stay in the South American Pacific archipelagos in early 1879, focusing on his representations of the Kawésqar men, women and territory; they are analysed in the context of the travelogues of the period. I do argue that the singularity of Vereker’s work is meaningful as it does produce a rather nuanced narrative, distant of the barbarizing rush of British authors as Fitz Roy, Cunnigham y Coppinger.